Evaluasi Keberterimaan Pengguna terhadap Sistem Informasi Akademik Politeknik Negeri Ujung Pandang - Nurul Andi Istiyana; Nurniah Nurniah; Siti Nafisah Azis; Muh Abid Nur (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2023)
Nowdays, academic information system is a resource that must be owned by every university, both public and private. The requirement for fast, precise and reliable information is a conditiont that must be fullfied. The PNUP or SIMPONI academic information system has been implemented since 2020 and is a new system that replaces the previous system. In its use, the role of educators (Tendik) becomes the most influential user in the data processing process. However, since it was implemented, there are still some obstacles and data integration that has not been optimal.This study is an explanatory research, aims to explain the causal relationship between research variables and test the hypothesis formulated using the TAM Model. Tests will be carried out on users of the Ujung Pandang State Polytechnic with data collection techniques in the form of interviews and questionnaires. While the data analysis method is PLS-SEM using SmartPLS.Based on the results of the study, 4 hypotheses were tested, 2 hypotheses were accepted, namely perceptions of ease of use towards attitudes to using technology and attitudes to using technology towards interest in using technology. This shows that SIMPONI is still not well received. The rejected hypothesis is the perception of usefulness towards the attitude of using technology and the interest in using technology towards the actual use of technology. Furthermore, it is hoped that PNUP will be more responsive in making improvements and adjustments to system constraints.